Security in the cyber age: an introduction to policy and technology - Reveron, Derek S. (Cambridge University Press, 2024)
Cyberspace is essential for socializing, learning, shopping, and just about everything in modern life. Yet, there is also a dark side to cyberspace: sub-national, transnational, and international actors are challenging the ability of sovereign governments to provide a secure environment for their citizens. Criminal groups hold businesses and local governments hostage through ransomware, foreign intelligence services steal intellectual property and conduct influence operations, governments attempt to rewrite Internet protocols to facilitate censorship, and militaries prepare to use cyberspace operations in wars. Security in the Cyber Age breaks-down how cyberspace works, analyzes how state and non-state actors exploit vulnerabilities in cyberspace, and provides ways to improve cybersecurity. Written by a computer scientist and national security scholar-practitioner, the book offers technological, policy, and ethical ways to protect cyberspace. Its interdisciplinary approach and engaging style make the book accessible to the lay audience as well as computer science and political science students